2001
DOI: 10.1046/j.1365-2141.2001.02609.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet glycoprotein IIb polymorphism, traditional risk factors and non‐fatal myocardial infarction in young women

Abstract: Summary. Several platelet glycoprotein polymorphisms have been associated with an increased risk of myocardial infarction (MI) in studies that included predominantly men. In a population-based sample of 68 Caucasian women , 45 years old with non-fatal MI and 346 demographically similar control subjects, we found an increased risk of MI among women who possessed at least one copy of the glycoprotein IIb Ser 843 allele compared with those lacking the Ser 843 allele (odds ratio 1´85; 95% confidence interval 1´03±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…Moreover, in another study no significant relation was found between the HPA-3 genotypes and the risk for thrombosis and restenosis after stent placement [8]. On the contrary, a small study on young women from the US found an association between HPA-3b and myocardial infarction in the presence of other risk factors [9]; women having the HPA-3b allele and being current smokers had a 10-fold increased risk for myocardial infarction. Finally, Reiner et al [18] observed an association between HPA-3b homozygosity and ischemic stroke in young women with risk factors for atherosclerosis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, in another study no significant relation was found between the HPA-3 genotypes and the risk for thrombosis and restenosis after stent placement [8]. On the contrary, a small study on young women from the US found an association between HPA-3b and myocardial infarction in the presence of other risk factors [9]; women having the HPA-3b allele and being current smokers had a 10-fold increased risk for myocardial infarction. Finally, Reiner et al [18] observed an association between HPA-3b homozygosity and ischemic stroke in young women with risk factors for atherosclerosis.…”
Section: Discussionmentioning
confidence: 97%
“…The HPA3a and 3b alleles encode for subunits that only differ at position 843 where Ile substitutes Ser. Most, but not all, of the studies agree that the HPA-1b allele represents an inherited risk predisposing to acute coronary syndromes [4][5][6], while the reports on the significance of the polymorphisms of the a subunit are rare [6][7][8][9]. Moreover there are no data on the significance of HPA-3 alleles in the genesis of ST segment elevation myocardial infarction (STEMI) or unstable angina/ non-ST segment elevation infarction (NSTEMI-UA).…”
Section: Introductionmentioning
confidence: 90%
“…Among these, one study contained two independent researches [13], and three studies explored HPA-2a/b and GP Ib α VNTR, simultaneously [5, 11, 16]. In addition, six studies enrolled community-based populations [8, 9, 12, 14, 21, 22], and the rest were controlled through hospital populations. Only two articles mentioned gene sequencing using a blind method [16, 20] (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it appears that the Pro33 polymorphism of glycoprotein IIIa alters human platelet aggregation, adhesion, and secretion, perhaps through the mechanism of increased signaling and cytoskeletal changes, leading to stabilization of platelet-platelet and/or platelet-extracellular matrix interactions (236). Another variant that has been studied in the GPIIb-IIIa gene is the Ile843Ser polymorphism that has been shown to be associated with increased risk of MI in young women in the presence of other risk factors (247), but other studies have shown negative results (248,249).…”
Section: Genetic Variants In Platelet Surface Receptorsmentioning
confidence: 96%